Moiré lattice of twisted bilayer graphene as template for non-covalent functionalization - Dierke, Tobias; Wolff, Stefan; Gillen, Roland; Eisenkolb, Jasmin; Nagel, Tamara; Maier, Sabine; Kivala, Milan; Hauke, Frank; Hirsch, Andreas; Maultzsch, Janina (Angewandte Chemie. International edition, 2025)
We present a novel approach to achieve spatial variations in the degree of non-covalent functionalization of twisted bilayer graphene (tBLG). The tBLG with twist angles varying between 5° and 7° was non-covalently functionalized with 1,4,5,8,9,11-hexaazatriphenylenehexacarbonitrile (HATCN) molecules. Our results show a correlation between the degree of functionalization and the twist angle of tBLG. This correlation was determined through Raman spectroscopy, where areas with larger twist angles exhibited a lower HATCN peak intensity compared to areas with smaller twist angles. We suggest that the HATCN adsorption follows the moiré pattern of tBLG by avoiding AA-stacked areas and attach predominantly to areas with a local AB-stacking order of tBLG, forming an overall ABA-stacking configuration. This is supported by density functional theory (DFT) calculations. Our work highlights the role of the moiré lattice in controlling the non-covalent functionalization of tBLG. Our approach can be generalized for designing nanoscale patterns on two-dimensional (2D) materials using moiré structures as a template. This could facilitate the fabrication of nanoscale devices with locally controlled varying chemical functionality.